Diffuse intrinsic pontine gliomas: the future of combination therapy with mTORC1/2 inhibitors and radiation - Garcia, Idoia; Aldareguia, Juncal; Matheu, Ander (Translational Cancer Research, 2017)
DIPGs, even though rare in adults, account for 10 percent of all childhood central nervous system tumors and comprise 75–80% of brainstem tumors in children.